1996
DOI: 10.3354/meps140187
|View full text |Cite
|
Sign up to set email alerts
|

Substantial open-ocean phytoplankton blooms to the north of South Georgia, South Atlantic, during summer

Abstract: Substantial open-ocean phytoplankton blooms in the Antarctic Zone to the northwest of South Georgia, South Atlantic are described. Chlorophyll a , nutrient and physical oceanography data, collected between 2 and 5 January 1994 and again 1 mo later between 2 and 4 February along a 450 km transect comprising 14 stations, are presented. The transect crossed the Subantarct~c and the Polar Front During the January transect survey, in 2 locations to the south of the Polar Front, average surface mixed-layer chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…These interpretations are not supported by recent findings, which suggest that the PF is consistently > 250 km to the north of South Georgia (Orsi et al 1995. However, there is some evidence that warm water eddies of PFZ origin may influence the South Georgia region from the west , Whitehouse et al 1996b). …”
Section: South Georgia In the Antarctic Circumpolar Currentmentioning
confidence: 69%
“…These interpretations are not supported by recent findings, which suggest that the PF is consistently > 250 km to the north of South Georgia (Orsi et al 1995. However, there is some evidence that warm water eddies of PFZ origin may influence the South Georgia region from the west , Whitehouse et al 1996b). …”
Section: South Georgia In the Antarctic Circumpolar Currentmentioning
confidence: 69%
“…High phytoplankton concentrations 冒41:0 mg m 脌3 脼 are found below 60 m in the study area (El-Sayed and Weber, 1982;Bianchi et al, 1992;Tre麓guer and Jacques, 1992;Smith et al, 1996;Whitehouse et al, 1996). Deep chlorophyll maxima have been observed mostly in the summer/fall in the Scotia Sea (El-Sayed and Weber, 1982), western Antarctic Peninsula (Bianchi et al, 1992;Tre麓guer and Jacques, 1992;Smith et al, 1996) and near South Georgia (Whitehouse et al, 1996); they are not observed during winter/spring (El-Sayed and Weber, 1982;Smith et al, 1996).…”
Section: Deep Chlorophyll Maximummentioning
confidence: 86%
“…Deep chlorophyll maxima have been observed mostly in the summer/fall in the Scotia Sea (El-Sayed and Weber, 1982), western Antarctic Peninsula (Bianchi et al, 1992;Tre麓guer and Jacques, 1992;Smith et al, 1996) and near South Georgia (Whitehouse et al, 1996); they are not observed during winter/spring (El-Sayed and Weber, 1982;Smith et al, 1996). Due to limited data this feature was not included in this modeling approach, although it may well be one additional food source available to krill in summer.…”
Section: Deep Chlorophyll Maximummentioning
confidence: 99%
See 1 more Smart Citation
“…The waters south of the SACCF, influenced by the Weddell -Scotia Confluence, are rich in nutrients, especially silicate; hence, eddies from the SACCF could be an important mechanism for the enhancement of local productivity (Whitehouse et al, 1996). The cold core eddy that was formed in OCCAM rejoined the SACCF after 1 month; data from the Southern Ocean Argo program (a global array of temperature/salinity profiling floats; Roemmich and Owens, 2000) should help to describe the characteristics and fate of these eddies in the ocean.…”
Section: Discussionmentioning
confidence: 99%